PENGEMBANGAN MATERI PELAJARAN SENI MUSIK DI SD DALAM RANGKA LITERASI MANUSIA UNTUK MENDUKUNG KURIKULUM OBE (OUTCOME BASE EDUCATION) BERBASIS CASE METHODE - Afriadi, Putra; Simanjuntak, Eva Betty; Silalahi, Natalia (Universitas Negeri Medan, 2023)
This article discusses strategies for developing music teaching materials that do not only focus on artistic aspects, but also consider human literacy as a key element in the learning process. Learning the art of music is not only a place to develop artistic skills, but also as a means to improve students' reading, writing and critical thinking abilities. In the context of the OBE Curriculum, the Case Method approach is used to present contextual and relevant learning. Case studies in learning the art of music not only cover technical aspects, but also relate them to real situations that allow students to apply their knowledge in the context of everyday life. The research results show that the development of music art teaching materials that combine human literacy and the Case Method can increase learning effectiveness. Students not only master musical arts skills, but also develop a deeper understanding of the relationship between musical arts and everyday life. This research contributes to the development of the music arts curriculum in elementary schools by strengthening the integration of human literacy in music arts learning.